(untitled) (Bangladesh Journal of Botany, 2025)
This study investigated the effects of drying service accessibility and technological advancement on rice farmers’ income using a spatial-technology-quality-income framework. Based on data from 465 farmers, the analysis showed that improved spatial accessibility and technological upgrades significantly increased net income. A one-minute reduction in travel time raised income by approximately 0.53 yuan per unit area, while a one-point increase in technology score led to a 145.7 yuan gain. Drying quality measured by mold rate served as a significant mediator. Each 1% reduction in mold rate corresponded to a 200 yuan increase in income. The benefits were more pronounced for large-scale farmers, highlighting the role of operational scale. Moreover, policy subsidies effectively boosted farmer income by 22% on average. These findings provide empirical support for targeted investment in drying infrastructure, technological improvements, and policy interventions to enhance the economic efficiency of post-harvest services and strengthen rural livelihoods. Bangladesh J. Bot. 54(3): 469-476, 2025 (September)